Strategi Penyediaan Perumahan Bagi Pekerja Industri Studi Kasus di Kabupaten Bekasi - Karnahadijati, Sukmawatty; zefri, zefri; supriyanto, budi (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2023)
The development of Bekasi Regency as one of the industrial centers has a comparative advantage and an attraction for migration. The population growth rate in Bekasi Regency reaches 147,200 people. From that numbers, Bekasi Regency is the highest area in West Java with a population growth of 4.7 percent. The high rate of population growth in Bekasi Regency is dominated by urbanites. There are at least 64 thousand new arrivals who are looking for work and living in Bekasi Regency every year. Bekasi Regency's lack of readiness in anticipating population growth with various motives and diversity is the main cause that triggers housing and settlement problems. This research is intended to identify and analyze the characteristics of industrial workers in the Jababeka V Industrial Estate in Bekasi Regency and to determine the role of stakeholders in providing housing for industrial workers. The analytical method used is narrative qualitative and descriptive qualitative methods, with techniques of analysis of the characteristics of industrial workers, policy analysis, analysis of stakeholder participation, and analysis of potential and obstacles in the provision of housing for industrial workers, so that the final result is a strategy of providing adequate and affordable housing for industrial workers. From the research results, it is found that the strategy for providing adequate and affordable housing for industrial workers is through the provision of owned houses by utilizing facilities for MBR and rental / owned flats in Industrial Estate locations by optimizing the allocation of housing land in Industrial Estates. In addition, the high price of land around the location of Industrial Estates requires integralistic efforts starting from the Government, Local Government, private sector and the community with capacity building and mutually beneficial collaboration